Job Insecurity, Sickness Presenteeism and the Moderating Effect of Workplace Health Promotion. Issue 11 (November 2020) - Schmidt, Kristin; Pförtner, Timo-Kolja
Abstract : Objective: This study examined the relationship between job insecurity and presenteeism, and the role of workplace health promotion as moderator in this association. Methods: We used data from 9525 employees from the sixth BIBB/BAuA* Employment Survey 2012 for the working population in Germany. Data analysis was performed with logistic regressions. Results: Job insecurity was associated with a higher risk of presenteeism, even after adjustment for control factors (OR = 1.25, CI: 1.01–1.53, P < 0.05). Workplace health promotion moderated this relationship: It no longer existed in companies with health promotion. Conclusions: The results suggest that employees with job insecurity are more likely to work despite feeling ill with the aim of securing their jobs. By establishing workplace health promotion, companies can protect their employees from that behavior in order to avoid negative long-term consequences.